Utilization Of Alum And Lemon Peel (Citrus limon L.) As A Natural Ingredient For Making Deodorant Spray - Nur Rahmayanti Afifah Sabri; Evi Mustiqawati; Ratih Nurwanti (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Body odor resulting from excessive sweating is a common concern that can negatively affect personal comfort and social interactions. Deodorant sprays are widely used to control body odor by inhibiting the growth of odor-causing bacteria. Lemon peel (Citrus limon L.) contains citric acid and other bioactive compounds with antibacterial properties, making it a promising natural ingredient for deodorant formulations. The addition of potassium aluminum sulfate (alum) may further enhance deodorant effectiveness through its antiperspirant properties. Objective: This study aimed to formulate deodorant sprays containing lemon peel extract (Citrus limon L.) at different concentrations and to evaluate their physical characteristics, safety, and suitability for topical application. Methods: An experimental study was conducted using deodorant spray formulations containing lemon peel extract at concentrations of 1%, 3%, and 5%. The formulations were evaluated through organoleptic testing, homogeneity testing, pH measurement, spray pattern assessment, drying time determination, and skin irritation testing. The results were analyzed descriptively to determine the quality and acceptability of each formulation. Results: All deodorant spray formulations containing lemon peel extract successfully met the established quality requirements. Organoleptic evaluation showed acceptable appearance, odor, and consistency, while homogeneity testing confirmed uniform distribution of ingredients. The pH values of all formulations were within the acceptable range for topical products. Spray pattern and drying time tests demonstrated satisfactory performance, and no signs of skin irritation were observed during safety evaluation. The results indicated that formulations containing 1%, 3%, and 5% lemon peel extract were safe and suitable for use as deodorant sprays. Conclusion: Lemon peel extract (Citrus limon L.) can be successfully formulated into deodorant spray preparations with satisfactory physical characteristics and safety profiles. The incorporation of lemon peel extract and alum produced formulations that met the required quality standards, highlighting their potential as natural and environmentally friendly alternatives for personal care products. These findings support the use of lemon peel extract as a promising natural ingredient in the cosmetic and personal care industry. Keywords: Deodorant Spray; Lemon Peel Extract; Citrus limon L.; Alum; Natural Cosmetics; Physical Evaluation